2015
DOI: 10.1097/dbp.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of Two-Year-Old Children Exposed to Metformin and Insulin in Gestational Diabetes Mellitus

Abstract: No differences in neurodevelopmental outcome were seen in 2-year-old children born to mothers with gestational diabetes mellitus (GDM) treated with insulin or metformin during pregnancy. The results suggest that children born to mothers with GDM and exposed to metformin in utero do not systematically need extensive formal neurodevelopmental assessment in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…In another follow-up study of infants exposed to metformin during pregnancies with gestational diabetes, children exposed to metformin weighed more at the age of 12 months, and were heavier and taller at 18 months, however, body composition was similar (368) as was motor, social and linguistic development. Studies looking at neurodevelopment showed similar outcomes between exposed and nonexposed infants at 2 years of age (369,370).…”
Section: Other Antihyperglycemic Agentsmentioning
confidence: 84%
See 1 more Smart Citation
“…In another follow-up study of infants exposed to metformin during pregnancies with gestational diabetes, children exposed to metformin weighed more at the age of 12 months, and were heavier and taller at 18 months, however, body composition was similar (368) as was motor, social and linguistic development. Studies looking at neurodevelopment showed similar outcomes between exposed and nonexposed infants at 2 years of age (369,370).…”
Section: Other Antihyperglycemic Agentsmentioning
confidence: 84%
“…In summary, long-term follow up from 18 months to 2 years indicate that metformin exposure in-utero does not seem to be harmful with regards to early motor, linguistic, social, (368), metabolic (367,368) and neurodevelopmental (369,370) outcomes. Longerterm follow up is not yet available.…”
Section: Other Antihyperglycemic Agentsmentioning
confidence: 87%
“…It is important to note that maternal metformin treatment in humans does not compromise neurodevelopmental outcomes when measured in two year old children [60, 61]. Our results show that metformin promotes preservation of fetal DHA (despite reduced maternal liver DHA) important for fetal/neonatal brain development.…”
Section: Discussionmentioning
confidence: 72%
“…The strongest predictors of birth weight >90 percentile, were maternal triglycerides and measures of blood glucose control at gestational week 36 37 . In a follow-up study, no adverse effects on neurological development was detected in Finnish children born to mothers that had received metformin in pregnancy, and who were followed-up until the age of 18 months 38 .…”
Section: Studies Of Metformin Therapy In Gdmmentioning
confidence: 99%